The Implementation of Card Sort Active Learning with Mind Mapping to Increase Students’ Learning Interest in Biology at the Students’ of VII-E SMP Negeri 5 Surakarta - Ninik Ambarini; Alvi Rosyidi; Joko Ariyanto (Universitas Sebelas Maret, 2013)
The purpose of this research is to improve students’ learning interest in biological study by applying of active learning Card Sort accompanied Mind Mapping strategy at the students of 5 Junior High School in class VII-E. This research was a classroom action research which the research design consist of two cycles. Each cycle consisted of four basic steps, they were planning, action, observation, and reflection. The data were collected by using questionnaire, observation, and interview methods. The data collected were arranged in the form of table and graph and then were analysed. The technics of analysing data that used in this research was qualitative analysis. The qualitative analysis described the data resulted from questionnaire, observation and interview during the action research. The conclusion of research obtained that the application of active learning Card Sort accompanied Mind Mapping can improve students’ learning interest in biological study. This matter seen from result of research proved that improvement each indicator of learn interest in biological study have earned to reach goals which have been determined that was 75%. Result of mean percentage of learn interest questionnaire pre-cycle was 68,64%, and last cycle was 76,71%. While result of mean percentage of learn interest observation pre-cycle was 30%, and last cycle was 81,67%. Research discontinued at second cycle considering goals have been reached. Key Words: Card Sort, Mind Mapping, Learning Interest